Early fetoscopic tracheal occlusion for extremely severe pulmonary hypoplasia in isolated congenital diaphragmatic hernia: preliminary results. (24th June 2013) - Ruano, R.; Peiro, J. L.; da Silva, M. M.; Campos, J. A. D. B.; Carreras, E.; Tannuri, U.; Zugaib, M.
ABSTRACT Objective To evaluate the effect of early fetoscopic tracheal occlusion (FETO) (22–24 weeks' gestation) on pulmonary response and neonatal survival in cases of extremely severe isolated congenital diaphragmatic hernia (CDH). Methods This was a multicenter study involving fetuses with extremely severe CDH (lung‐to‐head ratio < 0.70, liver herniation into the thoracic cavity and no other detectable anomalies). Between August 2010 and December 2011, eight fetuses underwent early FETO. Data were compared with nine fetuses that underwent standard FETO and 10 without fetoscopic procedure from January 2006 to July 2010. FETO was performed under maternal epidural anesthesia, supplemented with fetal intramuscular anesthesia. Fetal lung size and vascularity were evaluated by ultrasound before and every 2 weeks after FETO. Postnatal therapy was equivalent for both treated fetuses and controls. Primary outcome was infant survival to 180 days and secondary outcome was fetal pulmonary response. Results Maternal and fetal demographic characteristics and obstetric complications were similar in the three groups (P > 0.05). Infant survival rate was significantly higher in the early FETO group (62.5%) compared with the standard group (11.1%) and with controls (0%) (P < 0.01). Early FETO resulted in a significant improvement in fetal lung size and pulmonary vascularity when compared with standard FETO (P < 0.01). Conclusions Early FETO may improve infant survival by further increases of lung size and pulmonary vascularity in cases with extremely severe pulmonary hypoplasia in isolated CDH. This study supports formal testing of the hypothesis with a randomized controlled trial. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.